Differential actions of diacylglycerol acyltransferase (DGAT) 1 and 2 in regulating lipid metabolism and progesterone secretion of goose granulosa cells. Issue 202 (September 2020) - Hu, Shenqiang; Gao, Shanyan; Zhu, Jiaran; Gan, Xiang; Chen, Xi; He, Hua; Liang, Li; Hu, Bo; Hu, Jiwei; Liu, Hehe; Han, Chunchun; Kang, Bo; et al.
Highlights: Distinct expression profiles of DGAT1 and DGAT2 were identified in individual granulosa layers of goose follicles before and after selection. DGAT1 is less efficient than DGAT2 in promoting lipid accumulation in both undifferentiated- and differentiated granulosa cells. DGAT1 is negatively while DGAT2 is positively involved in regulation of progesterone production in undifferentiated granulosa cells. Abstract: Accumulating evidence shows that granulosa cells within both mammalian and avian ovaries have the ability to synthesize fatty acids through de novo lipogenesis and to accumulate triglycerides essential for oocyte and ovarian development. However, very little is known about the exact roles of key genes involved in the lipid metabolic pathway in granulosa cells. The goal of this study was to investigate the differential actions of diacylglycerol acyltransferase (DGAT) 1 and 2, which are recognized as the rate-limiting enzymes catalyzing the last step of triglyceride biosynthesis, in regulating lipid metabolism and steroidogenesis in granulosa cells of goose follicles at different developmental stages. It was observed that the mRNAs encoding DGAT1 and DGAT2 were ubiquitous in all examined granulosa cell layers but exhibited distinct expression profiles during follicle development. Notably, the mRNA levels of DGAT1, DGAT2, FSHR, LHR, STAR, CYP11A1, and 3βHSD remained almost constant in all except for 1–2 follicles within the 8−10 mm cohort, followed by an acute increase/decrease in the F5 follicles. At the cellular level, siRNA-mediated downregulation of DGAT1 or DGAT2 did not change the amount of lipids accumulated in both undifferentiated- and differentiated granulosa cells, while overexpression of DGAT2 promoted lipid accumulation and expression of lipogenic-related genes in these cells. Meanwhile, we found that interfering DGAT2 had no effect but interfering DGAT1 or overexpressing DGAT2 stimulated progesterone secretion in undifferentiated granulosa cells; in contrast, interference or overexpression of DGAT1/2 failed to change progesterone levels in differentiated granulosa cells but differently modulated expression of steroidogenic-related genes. Therefore, it could be concluded that DGAT1 is less efficient than DGAT2 in promoting lipid accumulation in both undifferentiated- and differentiated granulosa cells and that DGAT1 negatively while DGAT2 positively regulates progesterone production in undifferentiated granulosa cells.